Circulating microRNAs in plasma as potential biomarkers for the early detection of prostate cancer. Issue 6 (31st January 2018) - McDonald, Alicia C.; Vira, Manish; Shen, Jing; Sanda, Martin; Raman, Jay D.; Liao, Jason; Patil, Dattatraya; Taioli, Emanuela
Abstract : Background: MicroRNAs (miRNAs) have been linked to prostate cancer (PC) risk; however, their role as a screening biomarker for PC has yet to be determined. We examined whether circulating miRNAs in plasma could be potential biomarkers for the early detection of PC among men undergoing prostate needle biopsy. Methods: Men who had a prostate biopsy due to an abnormal screening test were recruited. Linear regression was used to examine the association between miRNAs in plasma and PC status and to model individual miRNA expression on serum PSA and age to calculate the partial correlation coefficient ( r ). Results: There were 134 men, aged 46‐86 years, included, with 66 men with a PC diagnosis (cases), eight men with no PC diagnosis but atypical lesion, and 60 men without a PC diagnosis (controls). The most statistically significant PC circulating miRNAs were miR‐381, miR‐34a, miR‐523, miR‐365, miR‐122, miR‐375, miR‐1255b, miR‐34b, miR‐450b‐5p, and miR‐639 after adjusting for age ( P ‐values ≤0.05); however, they were no longer statistically significant after P ‐value adjustment for multiple comparisons. MiR‐671‐3p was differentially expressed between black and white cases ( P ‐value = 0.03). Moderate positive correlations with serum PSA were observed for miR‐381 overall and among controls ( r = 0.43‐0.60; P ‐values ≤0.05) and miR‐34a among cases ( r = 0.46; P ‐value = 0.02). Conclusions: There was no miRNA associated with PC diagnosis after adjusting for age and P ‐values; however, moderate correlations between miRNAs and serum PSA were observed. Further investigation between miRNAs and PC risk is warranted in a larger population at high risk for PC.